The Mediating Role of Self-Stigma in Perceived Public Stigma and Attitudes Toward Mental Health Help-Seeking Among Adults in Malaysia - Yee Ching, Cheng; Motevalli, Saeid; Abu Talib, Mansor; Ishak, Zahari (International Journal of Education and Cognitive Sciences, 2022)
Purpose: Mental health stigma is one of the major barriers to mental health help-seeking and care. Public stigma gives rise to self-stigma (SS), and both stigma results in negative attitudes toward mental health help-seeking (ATMHHS). Subsequently, ATMHHS is further associated with future help-seeking behaviour. This research aims to study the mediating effect of SS on the relationship between perceived public stigma (PPS) and ATMHHS among Malaysian adults. The significance is to encourage mental health awareness related to mental health stigma as well as to contribute to literature on mental health stigma. Methodology: This study was a cross-sectional, correlational, and quantitative study, in which data was collected using online survey. 136 participants were selected as a sample of Malaysian adults aged 18-64 years old. Data was collected using Self-Stigma of Seeking Help Scale, Stigma Scale for Receiving Psychological Help, and Attitudes toward Seeking Professional Psychological Help Scale: Short Form. Findings: The results from Hayes PROCESS macro showed that SS was a significant predictor for ATMHHS, while PPS was not a significant predictor of ATMHHS, and SS fully mediated the relationship between PPS and ATMHHS. Conclusion: This study has shown that PPS indirectly brings negative impact on ATMHHS, while SS predicts negative ATMHHS, hence it is recommended that more research be conducted on mental health stigma related areas in order to raise awareness in Malaysian society.